2002
DOI: 10.1063/1.1499479
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic interchain aggregate domain formation in conjugated polymer films studied by third harmonic generation near-field scanning optical microscopy

Abstract: The electronic structure of conjugated polymer films is of current interest due to the wide range of potential applications for such materials in optoelectronic devices. A central outstanding issue is the significance of interchain electronic species in films of these materials. In this paper, we investigate the nature of interchain species in films of poly͓2-methoxy-5-͑2Ј-ethylhexyloxy͒-1,4-phenylene vinylene͔ ͑MEH-PPV͒ both before and after thermal annealing. Our investigation employs a combination of third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 78 publications
(136 reference statements)
2
47
0
Order By: Relevance
“…34,35,[42][43][44]64,65 Aggregate formation can occur in solutions already and in thin films of high molecular weight MEH-PPVs, which might cause chain orientation effects. 28,[36][37][38] Recently, we reported that the birefringence of thin MEH-PPV films increases strongly with M w , 34,35 ranging from nearly isotropic to almost two-dimensional chain orientation parallel to the layer plane. Consequently, the linear optical constants of the films, i.e., their absorption, refractive index and birefringence also increase significantly with M w .…”
Section: Introductionmentioning
confidence: 99%
“…34,35,[42][43][44]64,65 Aggregate formation can occur in solutions already and in thin films of high molecular weight MEH-PPVs, which might cause chain orientation effects. 28,[36][37][38] Recently, we reported that the birefringence of thin MEH-PPV films increases strongly with M w , 34,35 ranging from nearly isotropic to almost two-dimensional chain orientation parallel to the layer plane. Consequently, the linear optical constants of the films, i.e., their absorption, refractive index and birefringence also increase significantly with M w .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that thermal annealing of a conjugated polymer film can provide the necessary energy to allow the individual polymer strand to explore configuration space so that they can reorganize themselves towards forming lower energy structure. The amount of intermolecular interactions of the polymers will increase as a result of ordered packing [20]. In the present case, thermal treatment of the spincoated oligomer films above its melting point and then annealing at 120 or 70 8C or quenching at room temperature leads to the formation of supramolecular packing and growth of polymeric lamellae with higher order, as indicated in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…During the process of spincoating, the solvent is quickly evaporated so that the polymer chains are frozen in a random way and can form varieties of conformations. On the contrary, thermal annealing of the polymer films will provide the necessary energy to make the different conformations in the spincoated film converge to a similar morphology in which both the main chains and side chains of the polymers are packed in a more ordered fashion [20]. Among the conjugated polymers, rigid-rod poly(p-phenyleneethynylene)s (PPEs) and their corresponding oligo(pphenyleneethynylene)s (OPEs) are one of the most investigated materials because of their potential applications in polymer LEDs [21] and molecular electronics [7,22].…”
Section: Introductionmentioning
confidence: 98%
“…The same group [116] studied the formation and properties of the interchain species in more detail using a combination of the NSOM technique with third harmonic generation (THG). The goal of their study was to clarify the origin of the domains found in these materials, as described above, and separate the effects related to the excited states of the polymer molecules/aggregates, such as photoluminescence, from the effects related to the ground states of the these species, which can be probed by THG.…”
Section: Near-field Scanning Optical Microscopy (Nsom)mentioning
confidence: 99%